The pricing of academic journals - Aviv Nevo; Daniel L. Rubinfeld; Mark McCabe (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2006)
In this paper we investigate the claim that academic journals are too expensive. We estimate library demand for academic journals and ask if short run profit maximization by publishers can explain observed prices. Libraries purchase a portfolio of journals so to estimate demand we extend the standard discrete choice model, and estimation methods, to allow for a choice consisting of a subset of a larger set of journals. Unlike the discrete choice model, the model allows for both positive and negative cross-price effects. We estimate the model using library holdings data and find that on average prices in the industry are lower than what static pricing models predict. Furthermore, we simulate the effects of mergers and find that the likely unilateral effect of a merger is to lower prices.
Keywords: 330